Golden malicious - Connolly, Sheila (Connolly, Sheila. Orchard mystery., 2013)
While orchard owner Meg Corey dreads the labor of manual irrigation to stave off a drought, her boyfriend, Seth, couldn't be more excited about doing historic renovation on one of Granford's oldest houses. Tagging along as he picks up supplies is supposed to give Meg a much-needed break, but the trip turns rotten when she almost trips over a dead body at an old saw mill's forest reserve. But the body isn't the only frightening discovery she makes. A mysterious insect infestation seems to have migrated to the area, one that could bring serious harm to local woodlands. And it's up to Meg to find out what's behind this sudden swarm of trouble.